An experimental study of flow patterns pertinent to waxy crude oil-water two-phase flows. (8th June 2017) - Piroozian, Ali; Hemmati, Mahmoud; Ismail, Issham; Manan, Muhammad A.; Rashidi, Mohammad M.; Mohsin, Rahmat
Graphical abstract: Highlights: A new flow pattern map for a waxy crude oil and water is proposed. A layer of water-in-oil emulsion was evidenced for all the flow conditions. Entrance effect cannot be eliminated for waxy crude oils regardless of the design. New configurations were discovered for annular flows. The wax appearance temperature was affected by the emulsified water. Abstract: Flow patterns encountered during the flow of a waxy crude oil and water in a horizontal pipeline were experimentally studied at a temperature 4 °C greater than the wax appearance temperature (WAT). The visual observation technique along with the analysis of the associated pressure drops and free water measurement were used to identify the flow patterns and their transitions. Designing a specific multiphase flow test facility and applying a newly proposed technique for controlling the mixture temperature also allowed the examination of the recently discovered phenomenon regarding the effect of emulsified water droplets on accelerating the wax crystallization process above the WAT under dynamic conditions. The results of this study showed the deposition of wax crystals on the pipe wall for some of the flow patterns which, by implication, authenticates the influence of emulsified water on elevating the WAT even in dynamic flow conditions. Classification of the flow patterns based on the wax deposition yielded an original flow pattern map composed of nine patterns among which new configurations were evidenced for annular flows. In addition, all the flow patterns were affected by the entrance effect and a layer of water-in-oil emulsion was observed for all the flow conditions. The influential parameters in the formation of such flow patterns are theoretically discussed in details. Since the waxy crude oil in two-phase flow is a relatively uncharted area of study, the results of this study can provide a platform for furthering research.